PENGARUH KUALITAS LAYANAN, KEPUASAN DAN LOYALITAS PELANGGAN - Yulisetiarini, Diah (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2015)
Abstract: This research aims to analyze the effect of service quality on customer satisfaction and loyalty. Population of the research is all customers of conventional banks in Situbondo. Purposive sampling method was used with the sample consisted of 115 respondents. Results of path analysis test showed that physical evidence, reliability, responsiveness, empathy, assurance, and customer satisfaction had significant effect on customer loyalty. Keywords: Service Quality, Satisfaction, Loyalty